FEATURES OF CULTURAL ANALYZIS OF PHOTOS IN DEVELOPING INTERCULTURAL COMPETENCE OF STUDENTS IN LEARNING FOREIGN LANGUAGES - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
The article discusses the need to develop the visual aspect of intercultural competence, in particular visual cultural competence. This competence, in the aggregate of its structural and content components - cognitive, emotional and evaluative, activity, involves the development of strategies for students to work with cultural information presented in a visual way, in particular in photographic images.